Cyberbullying: legal regulations in Central Asia - POBEDINSKY, V. N.; SHESTAK, V. A.; VOROBUEV, N. S.; TRUNTSEVSKY, Y. V.; SEVALNEV, V. V. (Utopía y Praxis Latinoamericana, 2019)
ABSTRACT This study analyses the social and psychological determinants of cyberbullying and identifies the setting in which traditional face-to-face bullying transforms into virtual violence. The article also outlines the features influencing the manifestation of cyberbullying in the countries of Central Asia. Considering the flavour of traditionalism in the Asian culture and social relations, countries within the region should implement new institutions and foster cultural values in schoolchildren, with the focus kept on the prevention of cyberbullying. The juvenile justice system should keep up with the anti-cyberbullying trend because older children may be legally liable due to age and hence, carry punishment. RESUMEN El estudio actual analiza los determinantes sociales y psicológicos del acoso cibernético e identifica el entorno en el que el acoso cara a cara tradicional se transforma en violencia virtual. El artículo también describe las características que influyen en la manifestación del ciberacoso en los países de Asia Central. Teniendo en cuenta el sabor del tradicionalismo en la cultura y las relaciones sociales de Asia, los países de la región deberían implementar nuevas instituciones y fomentar los valores culturales en los escolares, con el foco puesto en la prevención del acoso cibernético. El sistema de justicia juvenil debe mantenerse al día con la tendencia contra el acoso cibernético porque los niños mayores pueden ser legalmente responsables debido a la edad y, por lo tanto, llevar castigo.